2017
DOI: 10.17305/bjbms.2017.2068
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF)-related single nucleotide polymorphisms rs10738760 and rs6921438 are not associated with diabetic retinopathy (DR) in Slovenian patients with type 2 diabetes mellitus (T2DM)

Abstract: Diabetic retinopathy (DR) is a complication of diabetes characterized by vascular permeability, increased tissue ischemia, and angiogenesis. One of the most important proteins involved in angiogenesis is vascular endothelial growth factor (VEGF, also known as VEGFA). A previous study demonstrated that two single nucleotide polymorphisms (SNPs), rs6921438 and rs10738760, account for nearly half the variation in circulating VEGF levels. The aim of our study was to assess the association between rs6921438 and rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Similarly, they did not observe significant effects of rs6921438 or rs10738760 on diabetic microvascular complications in patients with T2DM [31]. In line with these and our findings are also the results of another study on Slovenian patients with T2DM [32], which reported no significant association between DR and rs6921438 and rs10738760 polymorphisms. Overall, the results from our and the previous studies indicate a more complex and perhaps indirect relationship between VEGF and T2DM and its microvascular complications, as suggested by Bonnefond et al [31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, they did not observe significant effects of rs6921438 or rs10738760 on diabetic microvascular complications in patients with T2DM [31]. In line with these and our findings are also the results of another study on Slovenian patients with T2DM [32], which reported no significant association between DR and rs6921438 and rs10738760 polymorphisms. Overall, the results from our and the previous studies indicate a more complex and perhaps indirect relationship between VEGF and T2DM and its microvascular complications, as suggested by Bonnefond et al [31].…”
Section: Discussionsupporting
confidence: 91%
“…Overall they reported no significant association between the two VEGF-related SNPs and the risk of T2DM, DN or DR [31]. Similarly, Terzić et al [32] showed that rs6921438 and rs10738760 were not associated with DR in Slovenian patients with T2DM.…”
Section: Introductionmentioning
confidence: 96%
“…Vascular endothelial growth factor (VEGF) is a crucial cytokine used to promote the formation of new blood vessels, which may promote vascular endothelial cells, smooth muscle cell mitosis, vascular permeability, and angiogenesis [9, 10]. Previous studies on the association between VEGF and vascular disease revealed that serum VEGF was significantly increased in patients with diabetes mellitus, and the increase of VEGF was closely associated with the germination of diabetic angiopathy [11, 12]. The present study intended to investigate the vascular lesion of type 2 diabetes mellitus in Goto-Kakizaki (GK) rats and human umbilical vein endothelial cells, in order to illustrate the mechanism of the pathogenesis of the vascular lesion of type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…This study could only find an association of rs13207351 with NPDR and rs5742632 with PDR [107]. Similarly, studies performed in the Caucasian Slovenian and Mexican PDR subjects did not observe an association between AA genotype of rs6921438 or rs10738760 [108,109] and rs3025021, rs3025035, rs2010963, respectively [110]; however, recent studies have also shown that rs2010963 is associated with the development and severity of DR in Egyptian [111] and Sudanese [112] patients.…”
Section: Vegf Genementioning
confidence: 57%